2015
DOI: 10.1016/j.placenta.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of the placenta – From rodents to humans

Abstract: The placenta performs a wide range of physiological functions; insufficiencies in these functions may result in a variety of severe prenatal and postnatal syndromes with long-term negative impacts on human adult health. Recent advances in magnetic resonance imaging (MRI) studies of placental function, in both animal models and humans, have contributed significantly to our understanding of placental structure, blood flow, oxygenation status, and metabolic profile, and have provided important insights into pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 45 publications
1
40
0
3
Order By: Relevance
“…In mice, the function of the syncytiotrophoblast/vascular interface can be monitored non‐invasively in vivo by dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) (Plaks et al , ,b). This technique has been successfully implemented in studies of tetraploid placental complementation, fetal growth, implantation, and mouse models of pregnancy complications including intrauterine growth restriction (IUGR; Plaks et al , ,b; Solomon et al , ; Avni et al , ). In humans, IUGR is among the most frequent pregnancy complications associated with abnormalities in placental growth, structure, and function, and is a major cause of fetal morbidity and mortality (Regnault et al , ; Burton et al , ; Cox & Redman, ).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the function of the syncytiotrophoblast/vascular interface can be monitored non‐invasively in vivo by dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) (Plaks et al , ,b). This technique has been successfully implemented in studies of tetraploid placental complementation, fetal growth, implantation, and mouse models of pregnancy complications including intrauterine growth restriction (IUGR; Plaks et al , ,b; Solomon et al , ; Avni et al , ). In humans, IUGR is among the most frequent pregnancy complications associated with abnormalities in placental growth, structure, and function, and is a major cause of fetal morbidity and mortality (Regnault et al , ; Burton et al , ; Cox & Redman, ).…”
Section: Introductionmentioning
confidence: 99%
“…A range of MRI techniques have been proposed to examine the placenta, including anatomical measures using T 1 ‐ and T 2 ‐weighted, and diffusion‐weighted MRI; and functional measures using dynamic contrast enhanced MRI (DCE), arterial spin labeling (ASL), intravoxel incoherent motion (IVIM) imaging, and blood oxygen level‐dependent (BOLD) MRI . Excellent reviews can be found elsewhere . Particularly, the IVIM technique provides unique information about blood flow in the capillary and small vessels, without exogenous administration of a contrast agent, as required for DCE.…”
mentioning
confidence: 99%
“…13 Excellent reviews can be found elsewhere. 14,15 Particularly, the IVIM technique 16 provides unique information about blood flow in the capillary and small vessels, without exogenous administration of a contrast agent, as required for DCE. IVIM measures of the placental perfusion have been reported in human with normal or complicated pregnancy, 8,[17][18][19][20] and animal models with normal pregnancy.…”
mentioning
confidence: 99%
“…MRS can examine some aspects of placental metabolism but it requires long scan times and has limited resolution and spatial coverage. 10,[19][20][21] These weaknesses in current clinical placental assessment mean that decisions about clinical management of placental disease are made in the absence of any significant information about the metabolic state of the placenta.…”
mentioning
confidence: 99%